Recovery Of Gold From Low -Grade Ore Of Gua Musang, Kelantan Using Chenical And Biological Methods - Siti Nursyahirah Binti Razali f
Gua Musang, Kelantan has become a well-known site in gold mining history. However, conventional gold mining activities using chemicals had contributed to environmental damages and gave impacted the ecosystem worldwide such as water and land pollution because of the chemical that is being used. Therefore, this study has been carried out to determine the efficiency of the biological methods for gold recovery in low-grade ore of Gua Musang, Kelantan as a potential method for future approach in mining industry. In this study, we used Shewanella oneidensis MR-1 as an anaerobic metal reducing bacteria to reduce Iron (III) reduction and noble metal ions. Ferrozine assay was used to determine the concentration of ferrous iron with an optical density 562 nm. The highest amount of the deposited ore, 0.5 g/mL with MR-1 showed a significant result in a concentration of Ferrous Iron, 1.243 # 0.329 mM while the highest utilization of electron shuttle, 100 mg/L showed the result reached 1.611 ‡ 0.099 mM. In addition, the Aurum were extracted by using chemical method with a mixture of nitric acid and hydrochloric acid (1:3; v/v) and analysed by using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). For the results, the biological method showed recovery for Aurum in ore samples with the average recovery value 72 * 17.35 %. As conclusions, this study showed the biological methods has the potential to be used for gold extraction compared to chemical method.